Applied research in management - C. Orpen (South African Journal of Business Management, 1985)
The dominant model for research in management is the scientific one developed in the natural sciences. This ideal model is shown to differ in important ways from that followed by most applied researchers working on real-life management problems. It is argued that the dominant or ideal model has serious deficiencies when used to research many of the problems investigated by applied researchers. For improved understanding of management Issues, it is suggested that the model followed by applied researchers be adopted more often than is currently the case.
Keywords: 650